2000
DOI: 10.1210/endo.141.11.7785
|View full text |Cite
|
Sign up to set email alerts
|

Squirrel Monkey Immunophilin FKBP51 Is a Potent Inhibitor of Glucocorticoid Receptor Binding1

Abstract: Squirrel monkeys have high circulating cortisol to compensate for expression of low-affinity glucocorticoid receptors (GRs). We have demonstrated that the FK506-binding immunophilin FKBP51 is elevated in squirrel monkey lymphocytes (SML) and, in preliminary studies, have shown that squirrel monkey FKBP51 is inhibitory to GR binding. In this report, we have demonstrated that elevated FKBP51 is the unequivocal cause of glucocorticoid resistance in SML in the following ways: 1) FK506 increased GR binding in cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(56 citation statements)
references
References 44 publications
3
53
0
Order By: Relevance
“…Reynolds et al (16) showed that lymphocytes from squirrel monkeys, compared with human, have 13 times higher FKBP51 protein levels and incorporate more FKBP51 into GR complexes. Studies with transfected cells and cell-free approaches have clearly shown that squirrel monkey FKBP51 reduces GR hormone-binding affinity and expression of a reporter gene (16,17). Expressing human FKBP51 to similar levels resulted in some cortisol resistance, but to only one-fifth the extent caused by monkey FKBP51.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reynolds et al (16) showed that lymphocytes from squirrel monkeys, compared with human, have 13 times higher FKBP51 protein levels and incorporate more FKBP51 into GR complexes. Studies with transfected cells and cell-free approaches have clearly shown that squirrel monkey FKBP51 reduces GR hormone-binding affinity and expression of a reporter gene (16,17). Expressing human FKBP51 to similar levels resulted in some cortisol resistance, but to only one-fifth the extent caused by monkey FKBP51.…”
Section: Resultsmentioning
confidence: 99%
“…These receptors for glucocorticoids (GR) or progesterone (PR) must be assembled through an ordered pathway involving Hsp40, Hsp70, Hsp90, and an assortment of Hsp-binding cochaperones (14). A physiological consequence of FKBP51 incorporation into GR complexes was recently observed in New World primates such as squirrel monkeys (15)(16)(17)(18). These animals are hyposensitive to cortisol because of lowered GR hormone-binding affinity, similar to some clinical patients.…”
mentioning
confidence: 99%
“…There is ample evidence of genetic variation affecting GR-mediated regulation of the stress response. A promising candidate gene is FKBP5, which codes for a protein FK506 binding protein 5-51, a co-chaperone of the hsp90, and regulates the affinity of the GR for cortisol (Binder 2009;Denny et al 2000;Wochnik et al 2005). Recently, a strong stressinduced increase of FKBP5 mRNA in the central amygdala has been demonstrated (Scharf et al 2011), supporting the significance of FKBP5 regulation during central GR activation.…”
Section: Introductionmentioning
confidence: 98%
“…Termination of this response involves binding of glucocorticoids (i.e., cortisol) at the glucocorticoid receptor. FK506‐binding protein 51( FKBP5 ) acts as a functional negative regulator of glucocorticoid receptor sensitivity by reducing binding affinity4 and restricting nuclear translocation 5…”
Section: Introductionmentioning
confidence: 99%